The assessment of molecular markers for skin colour determination in the South African population - Slabbert, Nandi (Department of Pathology, 2018)
Molecular markers associated with skin colour need to be investigated to determine viability and discriminatory power within the SA population. The use of phenotyping as a tool to aid forensic investigation is becoming incorporated internationally and its use within SA needs to be considered. This project proposes to examine the association between skin colour and two markers, which have been identified as potentially problematic within mixed ancestry populations. This will be done through designing and analysing a multiplex SNaPshot genotyping assay and independent pigmentation measurements.